2016
DOI: 10.1007/s00414-016-1391-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of canine saliva using mRNA-based assay

Abstract: A dog saliva analysis in addition to a bite-mark analysis may be important for evidence when a crime involves a dog bite. In this study, the utility of detecting canine saliva-specific mRNAs to identify canine saliva was evaluated. Canine saliva swabs (n = 20), urine swabs (n = 20), body surface swabs (n = 20), whole blood samples (n = 10), human saliva (n = 20), human skin surface swabs (n = 20), and human whole blood (n = 20) were tested. The saliva-specific genes encoding statherin (STATH), carbonic anhydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…RNA (a molecule with lower stability than DNA, and thus higher temporal sensitivity) has, for example, been utilised to identify various bodily fluids at crime scenes (Vennemann and Koppelkamm 2010). In fact, mRNA forensic studies have demonstrated feasibility at detecting and distinguishing between skin, saliva, blood, and reproductive fluids (Haas et al 2009;Hanson and Ballantyne 2014;Nakanishi et al 2017) even in old, degraded samples (Zubakov et al 2009). Although only recently investigated, eRNA has shown promise at distinguishing living biodiversity with metabolically active microorganisms, to potential legacy DNA signals (e.g.…”
Section: Physical Originsmentioning
confidence: 99%
“…RNA (a molecule with lower stability than DNA, and thus higher temporal sensitivity) has, for example, been utilised to identify various bodily fluids at crime scenes (Vennemann and Koppelkamm 2010). In fact, mRNA forensic studies have demonstrated feasibility at detecting and distinguishing between skin, saliva, blood, and reproductive fluids (Haas et al 2009;Hanson and Ballantyne 2014;Nakanishi et al 2017) even in old, degraded samples (Zubakov et al 2009). Although only recently investigated, eRNA has shown promise at distinguishing living biodiversity with metabolically active microorganisms, to potential legacy DNA signals (e.g.…”
Section: Physical Originsmentioning
confidence: 99%
“…Infectious agents, such as Helicobacter spp., Bartonella spp., or rabies virus, have also been evaluated [ 4 6 ]. In addition, canine saliva has been used for quantification of acute phase proteins [ 7 ] and allergen measurements [ 8 ] and in forensic studies for canine mRNA determination [ 9 ]. Furthermore, recently, healthy dog saliva proteome has been characterized by shotgun proteomics, with the identification of 2,491 proteins and peptides [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Statherin is a salivary protein encoded by the STATH gene, which helps to control the formation of hydroxyapatite crystals and plays an important role in maintaining the tooth enamel in the oral cavity (Schwartz et al, 1992;Goobes et al, 2006). The STATH gene is expressed in the human, dog, and pig salivary gland (Schlesinger and Hay, 1977;Nakanishi et al, 2016), and it was confirmed that the messenger RNA (mRNA) of the Statherin (STATH) gene was present in saliva but absent in blood, semen, vaginal secretions, and menstrual blood (Tsai et al, 2018). Positive selection of the STATH gene is consistent with the observation that domestic pig produces more saliva than wild boars (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%